The roles of private practice midwives in Prevention of Mother-To-Child Transmission Program (PMTCT) in Bali Province, Indonesia - I Ketut Dwipayana; Pande Putu Januraga; Ni Made Dian Kurniasari (Universitas Udayana, 2020)
Background and purpose: Mother-to-child transmission of HIV has been one of the problems in HIV prevention. In Indonesia, private practice midwives (PPM) play an important role in maternal and child health services. The roles of PPM in HIV vertical transmission prevention through PMTCT have not yet clearly understood. This research aims to analyse the roles of PPM in Bali Province in the PMTCT program as well as the PPM’s characteristics, knowledge, and attitudes about the program. Methods: This study was a descriptive cross-sectional survey, conducted from March to May 2020. The study population was PPM in Bali Province. The samples obtained were 404 out of a total of 1,736 PPM (23% response rate). The variables studied included socio-demographic characteristics, services and resources characteristics, knowledge, attitudes, and the role of PPM in four PMTCT prongs. Data was collected via self-filled online questionnaires distributed through Indonesian Midwives Associations branches in every district/city in Bali Province. Data were analysed descriptively and differences in roles in PMTCT were analysed using the chi-square test. Results: Of the 404 PPM, 66.1% served childbirth (deliveries), 25.4% had served HIV-positive women, and 18.3% had served HIV-positive pregnant women. As many as 95.5% of PPM played a good role in prong 1, and 99.0% of PPM, who had served HIV positive patients, played a good role in prong 2, 3 and 4. Statistically significant determinants for good implementation of prong 1 of PMTCT by the PPM were indicated by ownership or access to PMTCT information media (p=0.026), experience of serving HIV positive women (p<0.00), and having served higher number of PMTCT patients (p=0.019). Conclusion: The PPM in Bali Province has played a good role inPMTCT, with a significant difference for good PMTCT implementation in prong 1 determined by the availability of information media, a history of serving HIV-positive women, and the number of PMTCT patients who have been served.